An overview of solar photovoltaic panels end-of-life material recycling - Chowdhury M.S.; Rahman K.S.; Chowdhury T.; Nuthammachot N.; Techato K.; Akhtaruzzaman M.; Tiong S.K.; Sopian K.; Amin N. (Elsevier Ltd, 2023)
Electronic Waste; Environmental management; Environmental technology; Laws and legislation; Oscillators (electronic); Photovoltaic cells; Recycling; Solar concentrators; Solar energy; Solar power generation; Thin films; End of lives; Environmental performance; Photovoltaic technology; Regulatory frameworks; Solar panels; Solar photovoltaic panels; Waste generation; Waste of electrical and electronic equipments; Solar cell arrays